PENINGKATAN DISIPLIN SISWA DALAM MENAATI TATA TERTIB DENGAN MENGGUNAKAN TEKNIK MODELLING MELALUI LAYANAN PENGUASAAN KONTEN DI SMPN 49 JAKARTA PADA SISWA KELAS 8 TAHUN AJARAN 2018-2019 - Renatha Ernawati; Afdal Afdal (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2018)
Discipline can be said as an activity or business that is made because it is considered important and done in order to achieve certain positive things. Discipline is part of the attitude and behavior that characterizes compliance with a rule or provision. Discipline means a demand for the implementation of a regular, the same and orderly life which is made an absolute price so that progress can be made and changes to things that are more positive and good. The research aims to obtain the stages of student discipline. When content is categorized as medium with a percentage of 66.6% after obtaining content mastery service, content mastery services increase to 77.6%, through the t test 2.04. The results obtained prove that content mastery services with modeling techniques can improve discipline in students. The study was a class 8 student at SMPN 49 Jakarta with a total of 32 respondents. The research conclusions were obtained tt 10.67 > t table-n using experiments. Population in this research using modeling techniques through mastery services Keyword: discipline, code of conduct, telkmile modeling, content improvement